Characteristics of Leprosy Chemoprophylaxis Recipeints in The Tirtayasa Public Health Center Area, 2023–2024 - Imaroh, Rifa; Lumaksono, Maria Angela; Imani, Izzah; Widasmara, Dhelya (UI Scholars Hub, 2026)
Leprosy remains a public health problem in Indonesia. In 2023, Indonesia ranked third globally in the number of leprosy cases, with 14,376 reported cases, after India (107,851 cases) and Brazil (22,773 cases). One of the key strategies for leprosy control in Indonesia is the implementation of preventive measures, including home visits and the administration of chemoprophylaxis using single-dose rifampicin (SDR). Post-exposure prophylaxis plays an important role in preventing leprosy transmission among contacts of confirmed patients. This study aimed to describe the characteristics of leprosy chemoprophylaxis recipients in the Tirtayasa Public Health Center area during 2023–2024. This study was an descriptive observational study. A total of 381 respondents were included using total sampling from close contacts of leprosy patients who received chemoprophylaxis. Data were analyzed descriptively. The majority of chemoprophylaxis recipients were aged ≥15 years (328 individuals; 86.1%). Most recipients were female (198 individuals; 52.0%). The highest number of recipients was found in Tirtayasa Village (81 individuals; 21.3%). Based on the type of contact, most recipients had neighbor contact (237 individuals; 62.2%). The most commonly administered rifampicin dose was 600 mg (326 individuals; 85.6%). No adverse effects were reported among all recipients following rifampicin administration. Most leprosy chemoprophylaxis recipients were aged ≥15 years and female. The majority of recipients resided in Tirtayasa Village and had neighbor contact with leprosy patients. Rifampicin at a dose of 600 mg was the most frequently administered, and no adverse effects were observed among all recipients. Keywords: Characteristics, Chemoprophylaxis, Leprosy